Reducing Emissions from Nepal’s Community Managed Forests: Discussion for CoP 14 in Poznan - Karky, Bhaskar Singh; Banskota, Kamal (Journal of Forest and Livelihood, 2009)
Community Forest Management (CFM) in developing countries has become an important topic in the global discourse on climate change. However, deforestation as a source of carbon emissions were largely ignored under the Kyoto Protocol (KP) and few opportunities appeared to be available for communities managing forests to benefit from this. Now there appear to be new opportunities arising for forests, and more specifically for CFM, under the proposed Reducing Emissions from Deforestation and Degradation (REDD) policy. This paper analyses the emission mitigating role of forests under the proposed REDD policy and tries to analyse some of the main issues that need to be addressed (and raised at CoP 14) to enable communities who are managing forests to benefit. The main areas to be addressed are: a) carbon accounting criteria, b) baseline construction, and c) indigenous people's rights. Suggested ways forward on all these are proposed. Keywords: REDD, CDM, CoP 14, community forest management, carbon trade Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.33-36